Are firm- and country-specific governance substitutes? Evidence from financial contracts in emerging markets - Bill Francis; Iftekhar Hasan; Liang Song (Bank of Finland, 2012)
We investigate how borrowers corporate governance influences bank loan contracting terms in emerging markets and how this relation varies across countries with different country-level governance. We find that borrowers with stronger corporate governance obtain favorable contracting terms with respect to loan amount, maturity, collateral requirements, and spread. Firm-level and country-level corporate governance are substitutes in writing and enforcing financial contracts. We also find that the distinctiveness of borrowers characteristics affect the relation between firm-level corporate governance and loan contracting terms. Our findings are robust, irrespective of types of regression methods and specifications.
URN:NBN:fi:bof-20140807127
Keywords: G20; G30; G31; G34; G38; 330